Recent Progress in Integrated CO2 Capture and Conversion Process Using Dual Function Materials: A State-of-the-Art Review - Chen, Jian; Xu, Yongqing; Liao, Peizhi; Wang, Haiming; Zhou, Hui (Carbon Capture Science & Technology, 2022)
CO2, despite its role as the primary greenhouse gas, is well-accepted as the most affordable and abundant nontoxic C1 source. Integrated CO2 capture and conversion (ICCC) is an emerging and promising process capable of reducing CO2 emissions and in-situ producing value-added products such as CH4 and syngas. This article reviews the recent research progress on the ICCC process, with an emphasis on the development of dual function materials (DFMs). The ICCC process with the combination of different CO2 catalytic conversions is first discussed from a thermodynamic point of view. The influence of operation parameters on the performance of DFMs is also summarized in detail. Then, the development of DFMs categorized by the catalytic component (i.e., Ni, Ru, etc.) is reviewed, including their performance and potential reaction mechanisms. Finally, the challenges and prospects of the ICCC process are highlighted.